Aetiology of Canine Infectious Respiratory Disease Complex and Prevalence of its Pathogens in Europe. (April 2020) - Day, M.J.; Carey, S.; Clercx, C.; Kohn, B.; MarsilIo, F.; Thiry, E.; Freyburger, L.; Schulz, B.; Walker, D.J.
Summary: The canine infectious respiratory disease complex (CIRDC) is an endemic worldwide syndrome involving multiple viral and bacterial pathogens. Traditionally, Bordetella bronchiseptica (Bb), canine adenovirus type 2 (CAV-2), canine distemper virus (CDV), canine herpesvirus (CHV) and canine parainfluenza virus (CPiV) were considered the major causative agents. Lately, new pathogens have been implicated in the development of CIRDC, namely canine influenza virus (CIV), canine respiratory coronavirus (CRCoV), canine pneumovirus (CnPnV), Mycoplasma cynos and Streptococcus equi subspecies zooepidemicus . To better understand the role of the different pathogens in the development of CIRDC and their epidemiological relevance in Europe, prevalence data were collected from peer-reviewed publications and summarized. Evidence of exposure to Bb is frequently found in healthy and diseased dogs and client-owned dogs are as likely to be infected as kennelled dogs. Co-infections with viral pathogens are common. The findings confirm that Bb is an important cause of CIRDC in Europe. CAV-2 and CDV recovery rates from healthy and diseased dogs are low and the most likely explanation for this is control through vaccination. Seroconversion to CHV can be demonstrated following CIRDC outbreaks and CHV has been detected in the lower respiratory tract of diseased dogs. There is some evidence that CHV is not a primary cause of CIRDC, but opportunistically re-activates at the time of infection and exacerbates the disease. The currently available data suggest that CIV is, at present, neither a prevalent nor a significant pathogen in Europe. CPiV remains an important pathogen in CIRDC and facilitates co-infection with other viral and bacterial pathogens. CnPnV and CRCoV are important new elements in the aetiology of CIRDC and spread particularly well in multi-dog establishments. M. cynos is common in Europe and is more likely to occur in younger and kennelled dogs. This organism is frequently found together with other CIRDC pathogens and is significantly associated with more severe respiratory signs. S. zooepidemicus infection is not common and appears to be a particular problem in kennels. Protective immunity against respiratory diseases is rarely complete, and generally only a reduction in clinical signs and excretion of pathogen can be achieved through vaccination. However, even vaccines that only reduce and do not prevent infection carry epidemiological advantages. They reduce spread, increase herd immunity and decrease usage of antimicrobials. Recommending vaccination of dogs against pathogens of CIRDC will directly provide epidemiological advantages to the population and the individual dog.